25 Stemi patients with ejection fraction 35 percent or less; percent improvement, average time to improvement and outcomes 2014–2017, 2017. (5th October 2017) - Blake, N; Lobo, R; Mannix, K; Ahern, C; Arnous, S; Abbas, S; Hennessy, T; Ullah, I; Brennan, A; Kiernan, T
Abstract : Introduction: Left ventricular ejection fraction (LVEF) is an independent risk factor for adverse cardiac outcomes post ST elevation myocardial infarction (STEMI). Post-STEMI patients can have lower than expected LVEF due to reasons other than myocardial necrosis owing to physiological aspects such as hibernation and stunning of myocardium. Much interest in the literature focuses on the months post infarction. This project attempts to assess the acute window in the weeks post STEMI where it is hypothesised there can be considerable improvement in LVEF. Methods: This retrospective study assessed follow up data on STEMI patients presenting to University Hospital Limerick (UHL) between January 2014 and January 2017. The study was initially presented to the UHL ethics committee and having being vetted was approved. An existing STEMI heartbeat database and PCI clinic database were used to identify the patient cohort estimated to be ten percent of STEMI cases based on an extensive literature review. Patients who had STEMI and had an inpatient transthoracic echocardiogram (TTE) showing LVEF of 35% or less were selected. Patients were excluded if they did not attend follow up in UHL or they did not have a repeat TTE done between 28 to 48 days post STEMI. Basic demographics, culprit vessel, time to follow up TTE as well as percentage improvement were recorded by accessing the patients electronic cardiology record comprising of TTE and coronary angiography reports via McKeeson Cardiology Software. Results: There were 634 STEMI cases presenting to UHL for primary percutaneous intervention (pPCI) during the study period. A total of 44 patients were identified to have a post-pPCI LVEF of 35% or less. 9 patients were excluded as they did not have repeat TTE within the requisite 48 day follow up period. 2 patients suffered fatal outcomes of death. 4 patients had not attended UHL for repeat TTE with repeat imaging at tertiary hospitals in Ennis and Nenagh respectively. Of the 29 patients with sufficient data, 83% (n=24) were male with the average age of 60.3 ±13.1 years. Culprit vessels were the left anterior descending artery in 83% (n=25) of patients, right coronary artery in 14% (n=4) patients and left circumflex artery in 3% (n=1). Average LVEF at baseline was 29.2% ±4.77%. Average time to repeat measurement was 37.4 ±5.3 days. There was an improvement in 20 patients, with an increase in LVEF of between 2.5% to 17.5%. 7 patients showed no improvement. 2 patients disimproved. This represents 69% of the cohort showing improvement within 48 days with a median increase in LVEF of 5% (interquartile range 15%). Conclusions: This small sample of STEMI patients shows promise for improvement in LVEF within 48 days post STEMI. This shows potential for improved cardiac function in the weeks rather than months post STEMI in line with concepts of stunning and hibernation of myocardium post myocardial infarction. It also provides an estimate on post STEMI low LVEF patients that may be candidates for alternative novel or research therapies.